Statistics : concepts and applications - Frank, Harry; Althoen, Steven C. (Cambridge [England] ; New York, NY, USA : Cambridge University Press, 1994)
Brings mathematical, theoretical and coneptual integrity to a body of topics and techniques that is appropriate to a first course in statistics.
Includes index.
On cover - Cambridge low price edition
oif 01/04/15, ijb 28/02/2019
Loans
Keywords: Statistics; Statistics - concept; Statistics - applications